Finansowanie działań politycznych w Japonii – zarys regulacji i praktyki ustrojowej - Misiuna, Jan (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2013)
This paper deals with the reality of political finance in Japan. In the text I describe how the election system influenced the process of creation of party system, especially segmentation of the Liberal-Democratic Party into factions. Consequences of this system include expensive election campaigns which in turn lead to close relationships between political parties and individual politicians and large, particularly corporate, donors. In effect the costs of election campaigns continue to increase and political parties, perpetually in need of money, constantly search for new donors. In this context it is not surprising that in Japan corruption is important problem. What is also important, however, is the fact that dysfunctional relationships between large, corporate donors and political parties were and are fundamental factors influencing economic policies of successive governments.